General dental practitioners' knowledge and attitudes on children's pain and pain management—A questionnaire survey. Issue 2 (10th May 2021) - Krekmanova, Larisa; Nilsson, Stefan; Hakeberg, Magnus; Klingberg, Gunilla; Robertson, Agneta
Abstract: The aim was to study general dental practitioners' knowledge and attitudes on pain and pain management in children and adolescents, using a multidimensional questionnaire. There is little information on dentists' views on pain in children. The research question was how attitudes and knowledge may correlate to the dentists' age, sex, years of professional experience, the proportion of working time devoted to treating children and adolescents, as well as being a parent. At the time of the study, 387 general dentists working for the Public Dental Service participated in a web‐based, multidimensional validated questionnaire holding the categories (A) views on the care of children in pain, (B) physiology, (C) pain alleviation, (D) medication, (E) sociology/psychology, (F) Pain assessment instruments and methods, (G) non‐medication methods of pain alleviation, and (H) documentation of pain management. The age categories were given as; below 25, 25‐35, 36‐45, 46‐55 years, and older than 55 years of age. 71% of the responders were female. The dentists' age cohort, as well as the years of professional experience, tended to make a difference as to the pain interventions in children and adolescents ( P  < 0.03). The female dentists, in comparison to the male dentists, conveyed different pain treatment strategies ( P  < 0.03). The proportion of working time devoted to treating children and adolescents, as well as being a parent, did not show significant differences regarding pain strategies. Associations were observed between the age of the dentists studied, the number of years as professionals and the knowledge and attitudes that benefit children's pain treatment. Being a parent was not significant. In this studied group, female dentists displayed significantly more care regarding pain management, than did their male colleagues. Furthermore, the study highlighted the need for a short questionnaire, user‐friendly yet with retained multidimensionality.